Trade and labor markets: Lessons from China's rise - David H. Autor (IZA World of Labor, 2018)
Economists have long recognized that free trade has the potential to raise countries' living standards. But what applies to a country as a whole need not apply to all its citizens. Workers displaced by trade cannot change jobs costlessly, and by reshaping skill demands, trade integration is likely to be permanently harmful to some workers and permanently beneficial to others. The “China Shock”—denoting China's rapid market integration in the 1990s and its accession to the World Trade Organization in 2001—has given new, unwelcome empirical relevance to these theoretical insights.
Keywords: 330; trade adjustment; manufacturing; non-college workers; China Shock